Safe obstetric anesthesia practice-COVID-19 - Thakur, Sunil; Kaushal, Sushruti; Kaur, Harpreet; Kaundal, Asmita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
COVID-19 or Corona virus disease 2019 was declared a pandemic by the WHO on 11th March 2020. Cesarean delivery is a commonly performed major surgery around the world. Important considerations while performing a cesarean section on a confirmed or suspected case of COVID19 are safety of the woman and the fetus; and prevention of transmission of SARS-CoV2 infection to the fetus as well as the healthcare providers. Woman and her birthing partner should be screened for the symptoms of COVID-19 before scheduled admission. Cesarean section in a woman suffering from COVID-19 should be managed by a multidisciplinary team consisting of anesthetists, obstetricians, labor and delivery nurses, neonatologist, critical care experts and infectious disease specialists, all members working in tandem with each other. General changes in workflow, reorganization of obstetric anesthesia services and proper use of personal protective equipment (PPE) are required for safe delivery of obstetric anesthesia during the COVID pandemic. Regional anesthesia is the preferred method of anesthesia for cesarean delivery. Using regional anesthesia reduces the need of aerosol generating procedures and avoids the use of mechanical ventilation. It also decreases the possibility of exacerbating the respiratory complications due to intubation. General anesthesia is recommended when a COVID-19 parturient presents with desaturation (oxygen saturation≤ 93%) for emergency cesarean delivery. Use of mechanical barriers around patient’s head during intubation and extubation might reduce exposure. The patient should be allowed to remain in the operating room itself till sufficiently recovered to be shifted directly to the isolation room.